Analyzing the job satisfaction among the employees of Export Import Bank Limited (EXIM BANK) - Anwar, Sumaiya (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.